2016
DOI: 10.7150/thno.15412
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Treatment Improves Mesenchymal Stem Cells Therapy by Preserving Stemness during Long-term In Vitro Expansion

Abstract: Mesenchymal stem cells (MSCs) are promising candidates for tissue regeneration and disease treatment. However, long-term in vitro passaging leads to stemness loss of MSCs, resulting in failure of MSCs therapy. Here, we report a melatonin-based strategy to improve cell therapy of in vitro cultured MSCs. Among four small molecules with anti-aging and stem cell-protection properties (rapamycin, resveratrol, quercetin and melatonin), colony forming, proliferation, and osteogenic differentiation assay showed that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
110
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(119 citation statements)
references
References 74 publications
(94 reference statements)
2
110
0
Order By: Relevance
“…55 Osteogenesis assay and adipogenesis assay were performed to detect the multi-potent differentiation of MSCs as we reported previously. 28 miRNA Microarray and Data Processing miRNA microarray of MSCs was performed using the LC Sciences microarray platform (LC Sciences) as described previously.…”
Section: Characterization Of Mscsmentioning
confidence: 99%
“…55 Osteogenesis assay and adipogenesis assay were performed to detect the multi-potent differentiation of MSCs as we reported previously. 28 miRNA Microarray and Data Processing miRNA microarray of MSCs was performed using the LC Sciences microarray platform (LC Sciences) as described previously.…”
Section: Characterization Of Mscsmentioning
confidence: 99%
“…The results revealed that melatonin treatment significantly inhibits regional resorption of alveolar bone and contributes to periodontal healing in this experimental periodontitis rat model . Moreover, several published reports indicate that melatonin stimulates bone formation …”
Section: Prospects and Conclusionmentioning
confidence: 62%
“…Furthermore, PL has been shown to provide an increase to the growth rates of MSC populations grown outside of fetal bovine serum, while still ensuring the chromosomal stability of the cell line over multiple generation. Moreover, additional trophic factors which improve the proliferation and differentiation of BM-MSCs into neurons and neuron-like cells in vitro have been identified, including melatonin, ATP, neurotrophin-3 (NT-3), rolipram, β-mercaptoethanol (BME), CHIR99021 (CHIR), lithium chloride, and others (Tu et al, 2014; Abdullah et al, 2016; Joe and Cho, 2016; Narcisi et al, 2016; Shuai et al, 2016; Yan et al, 2016). Co-culturing BM-MSCs with active neurons or culturing BM-MSCs on media conditioned by mature neurons also appears to promote their differentiation towards neural cell types (Tu et al, 2014; Kil et al, 2016).…”
Section: Identifying the Optimal Cell Type For Stem Cell Transplanmentioning
confidence: 99%